Thermo-mechanical damage modeling of a glass–phenolic composite material - Luo, Changsong; DesJardin, Paul E. (Composites science and technology, 2007)
This study is on the development of a thermo-mechanical damage model (TMDM) for glass–phenolic composite materials subject to high temperature and thermal radiative environments. The damaged composite is expressed as two regions of non-charred and charred materials. Homogenization methods are used to formulate the damaged material in terms of the volume fractions associated with composite fiber, resin and char. Equations are derived that employ Darcy’s law to account for the gas transport within the structure. Mechanical response of the composite is taken into account by solving a homogenized system of linear elasticity equations which introduces the gas-phase pressure in a self-consistent manner. A finite element method is developed to solve the thermal and mechanical equations for a two-dimensional clamped composite beam subject to thermal radiative heating. Overall, good agreement is obtained between the numerical predictions and experimental data for temperature and gas pressure. Results show the decomposition of the resin and char formation create local stress concentrations across the pyrolysis front. The origin of these stresses are from thermal expansion and contraction across the front and the generation of locally high pore gas pressures from resin decomposition.